Very Early MoCA Can Predict Functional Dependence at 3 Months After Stroke: A Longitudinal, Cohort Study - Abzhandadze, Tamar; Rafsten, Lena; Lundgren Nilsson, Åsa; Palstam, Annie; Sunnerhagen, Katharina S. (Frontiers in Neurology, 2019)
Introduction: After a stroke, cognitive impairment is commonly associated with poor functional outcomes. The primary aim of this study was to investigate if cognitive function, assessed with the Montreal Cognitive Assessment (MoCA) 36-48 h after stroke could predict functional dependence 3 months later. The secondary aim was to identify an optimal threshold for the MoCA score that could predict functional dependence. Materials and methods: This was a longitudinal cohort study. The research database from a stroke unit at Sahlgrenska University hospital was linked with the Swedish Stroke Register – Riksstroke. Cognitive function and Activities of Daily Living (ADL) were assessed with the MoCA and the Barthel Index (BI), respectively, 36-48 h after stroke. Functional outcome 3 months after stroke was studied with the modified Rankin Scale. The predictive characteristics of the MoCA were investigated using logistic regression analyses. Receiver Operating Characteristic curves (AUC) were used for identifying the optimal cut-off score on the MoCA for predicting functional dependence. The MoCA score which had equal sensitivity and specificity was chosen as the optimal score for predicting functional dependence. Results: A total of 305 participants were included in the study (mean age 68.8 years, n=179 men). The MoCA quartiles was a significant predictor of functional dependence 3 months after stroke as an individual variable (p<0.001, AUC = 0.72) and when adjusted for covariates such as age at stroke onset, living arrangement prior to stroke and ADL measured with BI within 36-48 h after stroke (p=0.01, AUC = 0.84). The MoCA score of ≤23 for impaired cognition had equal sensitivity and specificity for predicting functional dependence 3 months after stroke. Discussion and Conclusion: Cognitive function assessed with the MoCA within 36-48 h after stroke could predict functional dependence 3 months later. The participants with MoCA scores ≤23 for impaired cognition were more likely to be functionally dependent. Key words: Activities of daily living, Acute stroke, ADL, Cognition, Disability, Evaluation, Level of global disability, Modified Rankin Scale.